Efektivitas Pelaksanaan Shalat Subuh pada Mahasiswa PAI UIN Ar-Raniry Leting 2022 - Sulhan Yus; Ainal Mardhiah (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2024)
The implementation of dawn prayers is an obligation for Muslims who are sensible and mukallaf. Sometimes Muslims are very difficult to carry out the dawn prayer because the time of implementation is in the morning, where that time is the hours when humans are enjoying sleeping. This research was conducted to find out how the implementation of dawn prayers, obstacles, and efforts in carrying out dawn prayers in PAI students of the class of 2022. The research methods used are quantitative and qualitative approaches, where data collection uses interview, observation, and questionnaire techniques. The results of the study show that the implementation of dawn prayers for PAI students of the class of 2022 is quite good with a percentage of 73%. The implementation of dawn prayers for PAI students of the 2022 batch also sometimes experiences obstacles with a percentage of 53%. And PAI students of the class of 2022 also always make efforts to be able to carry out dawn prayers with a percentage of 77%.